2013
DOI: 10.5301/hipint.5000079
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Venous Thromboembolic Events following Femoroacetabular Osteoplasty: Aspirin is Enough for Most

Abstract: Aspirin is a safe and effective modality to provide thromboprophylaxis in patients undergoing hip-preservation surgery. The rate of VTE that we observed is, thus far, the lowest in comparison to other published series of hip preservation surgery that specifically focused on this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, multiple bone osteotomies during PAO may predispose patients for subsequent bleeding and a potent anticoagulation may increase the risk of bleeding [ 50 , 51 ]. On the other hand, because of the partial or non-weight bearing status of the patient after this procedure, some degree of inactivity and limb swelling occurs that may predispose the patients to VTE [ 16 , 52 ].…”
Section: Current Evidences Regarding Prevention Of Vte After Hpsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, multiple bone osteotomies during PAO may predispose patients for subsequent bleeding and a potent anticoagulation may increase the risk of bleeding [ 50 , 51 ]. On the other hand, because of the partial or non-weight bearing status of the patient after this procedure, some degree of inactivity and limb swelling occurs that may predispose the patients to VTE [ 16 , 52 ].…”
Section: Current Evidences Regarding Prevention Of Vte After Hpsmentioning
confidence: 99%
“…The only study that evaluates the incidence of VTE after min-open FAO is by Tischler et al [ 16 ]. In a prospective case series of 407 consecutive patients who underwent mini-open FAO procedure, the rate of symptomatic VTE was 0.25% when aspirin at 325 mg daily dose was administered.…”
Section: Current Evidences Regarding Prevention Of Vte After Hpsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no significant differences in symptomatic VTE rates in patients receiving warfarin, aspirin (ASA) 325 mg or ASA 81 mg, with no events of bleeding or hematoma formation 120 . In a prospective case series of 407 consecutive patients who underwent mini-open FAO procedure, Tischler et al 123 , found that the rate of symptomatic VTE was 0.25% when ASA 325 mg daily dose was administered. The majority of the patients included in this cohort were young, healthy and active, and were ambulated within hours of their surgery 123 .…”
Section: - Should Patients Undergoing Mini-open Femoroacetabular Oste...mentioning
confidence: 99%
“…In a prospective case series of 407 consecutive patients who underwent mini-open FAO procedure, Tischler et al 123 , found that the rate of symptomatic VTE was 0.25% when ASA 325 mg daily dose was administered. The majority of the patients included in this cohort were young, healthy and active, and were ambulated within hours of their surgery 123 . Based on institutional experience, a review study from the Rothman Institute recommended that ASA 81 mg two times daily is a safe and effective modality in minimizing the risk of VTE in patients undergoing hip preservation surgery 119 .…”
Section: - Should Patients Undergoing Mini-open Femoroacetabular Oste...mentioning
confidence: 99%